Gender equality in sport leadership: From the Brighton Declaration to the Sydney Scoreboard. (August 2016) - Adriaanse, Johanna A; Claringbould, Inge
This study investigated the development of the legacies of the five World Conferences on Women and Sport that have been convened by the International Working Group on Women and Sport from 1994 to 2010. In particular, it examined the ways in which gender is constructed in these legacies in relation to gender equality in sport leadership. The theoretical framework was drawn from Connell's four-dimensional gender model, which suggests that gender relations can be characterized in terms of four interwoven dimensions of social life: production, power, emotion and symbolism. The method used was a comparative case study of five legacies. We conducted a content analysis of documents relevant to the five legacies. Findings show that, in all five legacies, gender in relation to sport leadership was mainly constructed on the dimension of production and power relations (more women in leadership positions) and symbolic relations (creating a sporting culture that values women's participation at all levels). By contrast, the gendered dimension of emotional relations – collaboration between men and women – received limited attention. The implications of these findings for the acceleration of gender equality in sport leadership are discussed.